Organic fertilization with cow dung modulates growth, bioactive compounds, and antioxidant capacity in duckweed (Wolffia globosa) - Yadav, Nitesh Kumar; Patel, Arun Bhai; Rajesh S., Deepan; Parida, Pradyumn Kumar; Baidya, Sampa (Frontiers in Plant Science, 2026)
IntroductionWolffia globosa (wolffia) is a fast-growing aquatic plant rich in nutrients and bioactive compounds, whose biomass and functional quality are strongly influenced by fertilization. However, the effects of organic fertilizers on bioactive composition and antioxidant potential in wolffia remain poorly understood. This study fills this gap by evaluating fresh cow dung as an organic fertilizer and elucidating its novel role in enhancing biomass production, biochemical composition, bioactive compounds, and antioxidant capacity of wolffia.MethodsA randomized complete block design was employed with six treatments and three replications each. Treatments included an inorganic fertilizer control and five levels of cow dung applied at 10, 20, 30, 40, and 50 g L–1. Biomass yield was recorded, while biochemical composition (crude protein, crude lipid), bioactive compounds (total phenolics, flavonoids, carotenoids, tannins, ascorbic acid), and antioxidant activity (DPPH, ABTS, FRAP assays) were analyzed using standard protocols.ResultsBiomass was highest at 30 and 20 g L–1 cow dung, reaching 152.38 ± 12.25 g and 144.88 ± 1.28 g, respectively. Crude protein content was also highest at 40 g L–1 (30.40%) and in the control (29.31%). Crude lipid content peaked at 40 g L–1 (5.09%) and 50 g L–1 (4.91%). The highest total phenolic content (350.04 mg GAE g–1), total flavonoid content (159.35 mg QE g–1), and ascorbic acid (99.05 mg 100 g–1) were recorded at 50 g L–1 cow dung. In contrast, total carotenoid content (2286.90 µg g–1) and chlorophyll-b (11.82 µg g–1) were significantly higher in the control. Total tannin content did not differ significantly among the control, 10, and 50 g L–1 treatments, whereas the 20 and 30 g L–1 treatments exhibited reduced levels. Antioxidant activity was highest at 50 g L–1 for both DPPH (57.42%) and ABTS (65.65%) assays, while FRAP activity peaked at 10 g L–1 (180.64 μmol Fe g–1).DiscussionThe results demonstrate that cow dung enhances the bioactive compounds and antioxidant potential of wolffia. While medium doses (20–30 g L–1) maximized biomass production, higher cow dung levels, particularly 50 g L–1, promoted greater accumulation of phenolics, flavonoids, and overall antioxidant capacity.